Remote monitoring of the snow loads on a roof of buildings - V. A. Lobkina; I. A. Kononov; A. A. Potapov (Лëд и снег, 2016)
Obtaining actual data on a change in the value of snow load for a snowfall is an important task the solution of which is usually neglected. The purpose of the work was to obtain a data on dynamics of the snow load change on a roof for a snowfall. A system for remote monitoring of the snow load was developed for this purpose. This system allows continuous gathering and transmission of the data on the snow load change from a unit of area. Obtaining this information gives an indication of the size of snow loading and dynamics of the snow accumulation during snowfall. The developed system provides continuous collection and transmission of data about the changing snow load per unit area. This information makes possible judging values of the snow load and its dynamics during a snowfall. Using of this system allows monitoring of snow accumulation during a snowfall. Discreteness of the system is 1 minute, and the sensitivity to the load change is 50 g. The platform is designed for a load less than 100 kg. When a snowfall ends the platform should be cleaned. In 2015, the system has been just tested, but in future we plan to use the system without cleaning for the whole snow season. In this connection, the more powerful sensors will be used. The system consists of a rectangular platform with an area of 1 m2, and it is equipped with four load cells «TOQUES» BBA at the corners. It was used for two months from late January to mid-March. In total, nine snowfalls were observed. In the winter season of 2014/15, increases of snow loads changed within the range of 10–100 kg/m2. Analysis of the data shows that the maximum snow load exerted on the roof takes place at a snowfall peak, after that it decreases under the influence of external factors. Three main factors influencing formation of the snow loads on a flat roof are as follows: the quantity of solid precipitation, the snow melting, and redistribution of snow by wind. Using of the system allows obtaining actual values of snow load on roofs of buildings instead of data calculated from the snow weight on the ground. These values can be then used to correct standards for the snow loads.